Interactive Digital Manipulatives Using Wordwall to Enhance Elementary Students’ Interest and Learning Outcomes in Addition and Subtraction - Lusy Yuniastuti; Wasilatul Murtafiah; Lingga Nico Pradana (Postgraduate, University of Mataram, 2025)
This study aims to develop Wordwall-based interactive digital media to enhance second-grade students' interest and learning outcomes in addition and subtraction. Mathematics learning in elementary schools faces challenges, including low student interest and poor learning outcomes due to limited variation in teaching methods and media. This research employs the Research and Development (R&D) method using the ADDIE model (Analysis, Design, Development, Implementation, Evaluation) with 28 second-grade students as the subjects. Data collection techniques include observation, interviews, questionnaires, and tests. The developed media presents addition and subtraction through engaging educational games designed for students in the concrete operational stage, featuring virtual manipulatives that simulate hands-on learning experiences. Validation results show high media quality with expert ratings of 92% (material validity) and 88% (media validity). Learning interest increased significantly, with 89% of students responding positively to the interactive features. Learning outcomes improved substantially, with pre-test scores averaging 65.4, increasing to post-test scores of 84.2, and classical learning completeness rising from 57% to 89%. Statistical analysis (paired t-test, p < 0.05) confirms a significant improvement. This research demonstrates that Wordwall-based digital manipulatives effectively enhance both interest and achievement in elementary mathematics, contributing to the quality of education in the digital era.